PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL (Studi pada Perusahaan Go Public yang Tergabung dalam Indeks LQ45 Tahun 2012 dan 2013 di Bursa Efek Indonesia) (Students' Journal of Accounting and Banking, 2015)
This study aims to examine and analyze the influence of the characteristics of the company against of intellectual capital disclosure. This analysis uses the independent variable is the size of company, profitability, leverage, business age, ownership structure, independent commisioner and dependent variable of intellectual capital disclousure. The results of this research show that each variable has a different influence, namely the company's size, leverage, profitability, ownership structures and significant positive influence of paint against the disclosure of intellectual capital, the independent Commissioner gave a negative and significant influence, while giving the influential listing age positive and insignificant against of the intellectual capital disclosure. Conclusion the research indicates that the regression models that are formed with the independent variable which consists of company size, profitability, leverege, age listings, independent Commissioner and ownership structures can be used to predict the disclosure of intellectual capital in the company go public listed on the Indonesia stock exchange (idx) of the index LQ 45.Keywords: The Size of Company, Profitability, Leverage, Listing of Age, The Ownership Structure, Independent Commissioner and Intellectual Capital Disclosure